Imobilisasi Limbah Radioaktif Uranium Menggunakan Abu Batubara Sebagai Bahan Matriks Synroc - Gunandjar Gunandjar (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The Immobilization of Uranium Radioactive Waste Using Coal-Ash as Matrix Material of Synroc. The decommissioning of Phosphoric Acid Purification Facility – Petro Chemical of Gresik (PAPF-PCG) generates radioactive liquid waste containing uranium. The waste was treated by bio-oxidation process using bacteria for volume reduction of the waste to become radioactive sludge waste. The sludge waste contains uranium is included the classification of long-life alpha radioactive waste. The sludge waste must be immobilized by solidification process for preparation of disposal to ensure the safety of the environment in the present and future. In this research aim to immobilization of the radioactive sludge waste by solidification using coal-ash as matrix material of titanate synroc. Immobilization process was carried-out by mix the radioactive sludge waste with coal-ash and precursor oxides namely BaO, CaO, and TiO2 as addition of matrix materials. The composition of matrix material of synroc using coal-ash and addition of precursor oxides (in weight %) i.e : Al2O3 (6.26); BaO (5.33); CaO (10.52); TiO2 (68.02) ; and SiO2 (6.07). Beside that the matrix material contains oxides minor (in weight %) i.e : Fe2O3 (3.48), MnO2 (0.04), K2O (0.20) and Na2O (0.08). Waste loading in the waste synroc block was 30 weight %. The mixture then was dried at temperature of 130 oC, and calcined at 750 oC. The powder of calcination result then was pressed in the molder. Furthermore, the sintering process was carried out at the temperature of 900 – 1300 o C for 3 hours to form the solid multiphase ceramic of synroc block. As a comparison was done immobilization process using matrix material of standard synroc. The quality of the synroc block produced from immobilization was determined by testing of density, compressive strength, and leach-rate ((the accelerated leach-rate at temperature of water 100 oC)). The test results showed that the best quality of waste synroc block was obtained at the sintering temperature of 1100 oC for 3 hours with values of density 2.28 g/cm3, compressive strength 5.57 kN/cm2, and leach-rate of uranium is 1.05x10-6 g.cm-2.day-1. This leach-rate of uranium is lower than the standar waste synroc block 1.17x10-5 g.cm-2.day-1. The quality of the waste synroc block produced by sintering process has fulfill the recommendation of IAEA.